Battery positive plate and battery
By using a three-dimensional conductive network adhesive based on phenylboric acid-modified polyacrylic compounds and hydroxylated carbon nanotubes in lithium-ion batteries, the shortcomings of traditional adhesives in the structural stability, electrochemical performance and safety of the electrode sheet are solved, and higher battery cycle life and discharge performance are achieved.
Patent Information
- Application Number
- CN202411838376.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The electrode sheet structure in existing lithium-ion batteries is unstable, the electrode sheet surface is deteriorated, the electrochemical performance is not ideal, and the safety is low. In particular, the mechanical properties, conductivity and interface stability of traditional adhesives are insufficient, which limits the cycle life and safety of the battery.
A three-dimensional conductive network adhesive obtained by crosslinking polyacrylic compounds based on phenylboric acid compounds and hydroxylated carbon nanotubes is used to form a boroxane structure through multiple crosslinking mechanisms and self-crosslinking to improve the mechanical strength and conductivity of the adhesive.
It improves the mechanical strength, conductivity, cycle performance and stability of the battery positive electrode sheet, extends the cycle life of the battery, improves the discharge performance and fast charging and discharge ability, and reduces the consumption of electrolyte.
Smart Images

Figure BDA0005187341410000051 
Figure BDA0005187341410000061 
Figure BDA0005187341410000071
Abstract
Description
Technical Field
[0001] The invention relates to a battery, in particular to a battery positive electrode sheet and a battery. Background Art
[0002] With the steady growth of electric vehicle sales in the past few years, lithium-ion batteries play a vital role in moving towards a more efficient "energy future" due to their high energy and power density. Despite the above advantages, lithium-ion batteries must overcome the problems of unstable pole structure, pole surface degradation, unsatisfactory battery electrochemical performance, and low battery safety in order to be practically used in commercial batteries. Generally speaking, the binder in the pole piece has an extremely low mass ratio, which has a profound impact on the safety and electrochemical performance of lithium-ion batteries. It is a simple and effective way to improve the above problems.
[0003] Binder is an important component of battery electrode sheet, which can enhance the contact between active material, conductive agent and current collector, and maintain good stability. Existing traditional binders usually use polymer matrix, such as polyvinylidene fluoride (PVDF). Although these traditional binders can achieve effective bonding between positive electrode materials and electrode current collectors to a certain extent, they have some limitations: 1. Limited bonding effect and mechanical properties: Traditional binders have poor mechanical strength and flexibility, especially under high energy density and high current density conditions, they are prone to breakage or peeling, which limits the cycle life and safety of the battery. In addition, traditional binders are bonded by van der Waals force, and weak van der Waals force leads to poor bonding effect of the pole piece. 2. Insufficient conductivity: The low conductivity of traditional binders will lead to increased internal resistance of the battery, limiting the discharge performance and rapid charge and discharge capabilities of the battery. 3. Poor interface stability: The interface stability between traditional binders and positive electrode active materials is poor, and interface reactions or electrolyte penetration are prone to occur, resulting in decreased battery performance and increased consumption of electrolyte. Summary of the invention
[0004] The present invention aims at the above-mentioned problems, makes up for the deficiencies of the prior art, and provides a battery positive electrode sheet and a battery.
[0005] In a first aspect, the present invention provides a positive electrode sheet for a battery, comprising a positive electrode active material and a binder, wherein the binder is a product obtained by cross-linking a polyacrylic acid compound modified by a phenylboronic acid compound and hydroxylated carbon nanotubes.
[0006] The battery positive electrode sheet of the present invention adopts a three-dimensional conductive network binder based on the cross-linking of phenylboronic acid compounds modified polyacrylic acid compounds and hydroxylated carbon nanotubes. The binder utilizes the multiple cross-linking mechanism between phenylboronic acid groups and hydroxylated carbon nanotubes (OHCNT) and positive electrode active particles, as well as the self-cross-linking between phenylboronic acids to form a cycloboroxine structure, forming a special three-dimensional conductive network structure, thereby improving the mechanical strength, electrical conductivity, cycle performance and stability of the binder, further improving the discharge performance and rapid charge and discharge capabilities of the battery, and reducing the consumption of electrolyte, thereby forming a more stable electrolyte interface (CEI) film containing B, thereby extending the cycle life of the battery.
[0007] Specifically, in some embodiments of the present invention, the mass ratio of the phenylboric acid compound to the polyacrylic acid compound is 0.19-1.33; more specifically, the mass ratio of the phenylboric acid compound to the polyacrylic acid compound is 0.19, 0.38, 0.57, 0.76, 0.95, 1.14, 1.33; preferably, the mass ratio of the phenylboric acid compound to the polyacrylic acid compound is 0.57-0.95.
[0008] Specifically, in some embodiments of the present invention, the mass ratio of the polyacrylic acid compound modified by the phenylboric acid compound to the hydroxylated carbon nanotubes is 1.0-6.0. More specifically, the mass ratio of the polyacrylic acid compound modified by the phenylboric acid compound to the hydroxylated carbon nanotubes is 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0; preferably, the mass ratio of the polyacrylic acid compound modified by the phenylboric acid compound to the hydroxylated carbon nanotubes is 2.0-3.0.
[0009] In the present invention, a too large mass ratio of the phenylboronic acid modified polyacrylic acid compound to the hydroxylated carbon nanotubes will result in an excessively large crosslinking density, making the polymer network complicated, resulting in an excessively high slurry viscosity and inability to disperse evenly. A too small mass ratio will result in the polymer being unable to adapt to the expansion of the silicon negative electrode volume, resulting in poor cycle performance of the battery.
[0010] Specifically, in some embodiments of the present invention, the raw materials of the adhesive also include an activator, and the mass ratio of the activator to the polyacrylic acid compound is 0.53-1.60. More specifically, the mass ratio of the activator to the polyacrylic acid compound is 0.53, 0.79, 1.06, 1.32, or 1.60; preferably, the mass ratio of the activator to the polyacrylic acid compound is 0.79-1.32.
[0011] In the present invention, the crosslinking degree of the polyacrylic acid modified by the phenylboronic acid compound is regulated by controlling the mass ratio of the activator to the polyacrylic acid compound. When the content of the activator is too high, the crosslinking degree of the polyacrylic acid modified by the phenylboronic acid compound will also be too high, which will cause the positive electrode particles, the conductive agent and the binder to be unable to disperse during the homogenization process, so that the uniformity of the pole piece cannot be kept consistent, thereby affecting the improvement of the binder and battery performance. When the content of the activator is too low, the crosslinking degree of the polyacrylic acid modified by the phenylboronic acid compound is too low, making the viscosity of the positive electrode slurry very low, causing the slurry to have fluidity during the coating process, and it cannot be coated evenly, thereby affecting the improvement of the binder and battery performance.
[0012] Specifically, in some embodiments of the present invention, the activator is at least one of 1-ethyl-(3-dimethylaminopropyl)carbodiimide, dicyclohexylcarbodiimide, and N,N'-diisopropylcarbodiimide.
[0013] Specifically, in some embodiments of the present invention, the mass ratio of the positive electrode active material to the binder is 92:8-98:2; specifically, the mass ratio of the positive electrode active material to the binder is 92:8, 93:7, 94:6, 95:5, 96:4, 97:3, 98:2; preferably, the mass ratio of the positive electrode active material to the binder is 94:6-97:3.
[0014] Specifically, in some embodiments of the present invention, the phenylboronic acid compound is at least one of 3-aminophenylboronic acid, 2-aminophenylboronic acid, 4-aminophenylboronic acid, [3-(2-aminoethyl)phenyl]boric acid, and 3-aminomethylphenylboronic acid.
[0015] Specifically, in some embodiments of the present invention, the polyacrylic acid compound includes at least one of polyacrylic acid, polymethacrylic acid, sodium polyacrylate, lithium polyacrylate, sodium polymethacrylate, and lithium polymethacrylate.
[0016] Specifically, in some embodiments of the present invention, the polyacrylic acid compound modified by the phenylboronic acid compound is cross-linked with the hydroxylated carbon nanotubes, comprising:
[0017] S1. Dissolve a polyacrylic acid compound and a base in water, add an aqueous solution of a phenylboric acid compound to obtain a mixed solution, cool the mixed solution to 2°C-7°C, add an activator, and react for 10-14 hours to obtain a polyacrylic acid compound modified with a phenylboric acid compound;
[0018] S2: adding hydroxylated carbon nanotubes and dispersant into water and ultrasonicating for 1-3 hours to obtain a dispersion, and mixing the dispersion with the polyacrylic acid compound modified with the phenylboronic acid compound.
[0019] Compared with the traditional binder preparation process, the present invention adopts a three-in-one formula design of binder, conductive agent and solvent, simplifies the synthesis process, improves the preparation efficiency, and makes the technical solution have significant potential for direct industrial application.
[0020] Specifically, in some embodiments of the present invention, the positive electrode active material includes at least one of lithium iron phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide.
[0021] Preferably, in some embodiments of the present invention, the lithium cobalt oxide is LiCoO2; the lithium nickel oxide is LiNiO2; the lithium manganese oxide is Li2Mn2O4; the lithium nickel manganese oxide is LiNi 0.5 Mn 1.5 O4; the lithium nickel cobalt manganese oxide is LiNi 0.33 Co 0.33 Mn 0.33 O2.
[0022] Specifically, in some embodiments of the present invention, the base is at least one of lithium hydroxide, sodium hydroxide, and potassium hydroxide.
[0023] In a second aspect, the present invention also provides a method for preparing a positive electrode sheet of a battery, comprising the following steps: using a mixer to evenly mix the positive electrode active material and the binder to obtain a positive electrode slurry, using a coating machine to coat the positive electrode slurry on the surface of the current collector, and obtaining the positive electrode sheet of the battery after drying and cutting, wherein the active material loading is about 10-15 mg·cm -2 .
[0024] The present invention also provides a battery, comprising the above-mentioned battery positive electrode sheet, wherein the battery is a lithium ion battery, a semi-solid battery or a solid-state battery.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The present invention provides a positive electrode sheet for a battery, which uses a three-dimensional conductive network binder based on cross-linking of a polyacrylic acid compound modified by a phenylboronic acid compound and a hydroxylated carbon nanotube. The binder utilizes a multiple cross-linking mechanism between phenylboronic acid groups and hydroxylated carbon nanotubes (OHCNT) and positive electrode active particles, as well as self-cross-linking between phenylboronic acids to form a BOB structure, thereby forming a special three-dimensional conductive network structure, improving the mechanical strength, electrical conductivity, cycle performance and stability of the binder, further improving the discharge performance and rapid charge and discharge capability of the battery, and reducing the consumption of electrolyte to form a more stable electrolyte interface (CEI) film, thereby extending the cycle life of the battery.
[0027] (2) In the present invention, the crosslinking degree of the phenylboronic acid compound-modified polyacrylic acid compound is regulated by controlling the mass ratio of the activator to the polyacrylic acid compound, thereby improving the peel force, interfacial peel strength, viscosity, conductivity of the binder and the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The schematic diagram of the synthesis of the modified polyacrylic acid compound modified by 3-aminophenylboronic acid in Example 1;
[0029] Figure 2 This is a schematic diagram of the binder synthesis principle in Example 1;
[0030] Figure 3 This is the infrared detection spectrum of the polyacrylic acid compound modified by phenylboronic acid compound;
[0031] Figure 4 This is the infrared detection spectrum of the binder. DETAILED DESCRIPTION
[0032] The following will be combined with the accompanying drawings in the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.
[0033] Example 1
[0034] This embodiment provides a positive electrode plate for a battery, comprising a LiCoO2 active material and a binder, wherein the binder is a cross-linked product of a polyacrylic acid compound modified by a phenylboronic acid compound and a hydroxylated carbon nanotube.
[0035] Preparation of binder:
[0036] S1 Take 1g polyacrylic acid (PAA) and 0.05g LiOH and dissolve them in 20g water, add 0.76g 3-aminophenylboronic acid (APBA) to obtain a mixed solution, cool the mixed solution to 4°C and add 1.06g 1-ethyl-(3-dimethylaminopropyl)carbodiimide, and keep it at 4°C for 12 hours. Purify it by dialysis to obtain 3-aminophenylboronic acid modified polyacrylic acid. The synthesis principle is as follows Figure 1 shown.
[0037] S2: 0.3 g of hydroxylated carbon nanotubes (OHCNT) and 0.33 g of dispersant were added to 15.75 g of water and ultrasonicated for 2 hours to obtain a hydroxylated carbon nanotube dispersion. 0.75 g of 3-aminophenylboronic acid-modified polyacrylic acid was mixed with the hydroxylated carbon nanotube dispersion to obtain a binder (PBO). The synthesis principle is as follows: Figure 2 shown.
[0038] Preparation of positive electrode sheet: The positive electrode active LiCoO2 and binder were mixed and stirred in a mass ratio of 95:5 using a blender to obtain a positive electrode slurry with suitable viscosity. The slurry was coated on the copper current collector using a coater. After vacuum drying at 120°C for 12 hours, the positive electrode was cut into discs with a diameter of 12 mm. The positive loading of active material was about 13.0 mg cm -2 .
[0039] Half-cell preparation: The electrochemical performance was evaluated by half-cells assembled by sandwiching a separator (about 25 μm) between the above binder-based working electrode and a lithium foil counter electrode.
[0040] In this embodiment, the infrared detection results of polyacrylic acid modified with 3-aminophenylboronic acid are as follows: Figure 3 As shown, at 2877cm -1 The absorption peak at 1465 cm represents the stretching vibration of the CH bond of the benzene ring. -1 The absorption peak at 1350cm is the in-plane deformation vibration of the NH bond. -1 The absorption peak represents the stretching vibration of the BO bond, proving that 3-aminophenylboronic acid successfully modified polyacrylic acid.
[0041] The infrared detection results of the adhesive are as follows: Figure 4 As shown, the binder is at 1231cm -1 The absorption peak represents the stretching vibration of BOC, 735cm -1 The absorption peak represents the stretching vibration of BOB, proving the successful combination of 3-aminophenylboronic acid modified polyacrylic acid and OH-CNT.
[0042] Example 2-35
[0043] This example is used to compare and illustrate the lithium-ion battery disclosed in the present invention, and includes most of the operating steps in the above-mentioned Example 1, and the difference lies in: the synthesis conditions of the negative electrode active material, the polyacrylic acid compound modified by the phenylboronic acid compound and the binder, the synthesis components of the polyacrylic acid compound modified by the phenylboronic acid compound and the binder, and their masses and mass ratios are shown in Table 1.
[0044] Comparative Example 1
[0045] Compared with Example 1, the binder used in this comparative example directly mixes polyvinylidene fluoride and the conductive agent, and the rest is consistent with Example 1.
[0046] Table 1
[0047]
[0048]
[0049]
[0050]
[0051] The performance testing method of the lithium ion batteries in Examples 1-35 and Comparative Example 1 is as follows: Experiment 1:
[0052] Peeling test of positive electrode sheet: The peeling force and interfacial peeling strength of the positive electrode sheets in Examples 1-35 and Comparative Example 1 were tested using an electronic tensile testing machine in accordance with the national standard GB / T 2792-2014 “Test method for peeling strength of adhesive tape”. The test results are shown in Table 2.
[0053] Experiment 2
[0054] Viscosity test of positive electrode slurry: The viscosity of the positive electrode slurries in Examples 1-35 and Comparative Example 1 was tested using a digital viscometer. The test results are shown in Table 2.
[0055] Experiment 3
[0056] Conductivity test (measured by four-probe method): The adhesives of Examples 1-35 and Comparative Example 1 were coated on a PE film using a 100 μm scraper, and a conductive film was obtained after drying, and a conductivity test was performed.
[0057] Experiment 4
[0058] Cycle performance test: At 25°C, charge at a constant current rate of 0.2C to a voltage of 4.35V, then charge at a constant voltage of 4.35V to a current of 0.05C, and then discharge at a constant current rate of 0.2C to a voltage of 3.0V. This is a charge and discharge cycle process, and repeat this charge and discharge cycle process 100 times. The capacity retention rate after 100 cycles = discharge capacity after the 100th cycle / discharge capacity after the first cycle × 100%. The test results are shown in Table 2.
[0059] Table 2
[0060]
[0061]
[0062] It can be seen from the data in Table 2 that: from the battery test performance of Examples 1-35 and Comparative Example 1, it can be seen that the three-dimensional conductive network binder based on phenylboronic acid compounds modified polyacrylic acid compounds and cross-linked hydroxylated carbon nanotubes used in the present invention has better peeling force, interface peeling strength, viscosity (Pa·s), and conductivity than the polyvinylidene fluoride binder in Comparative Example 1, and the cycle performance and stability of the prepared battery are also better than the battery prepared in Comparative Example 1, indicating that the binder of the present invention utilizes the multiple cross-linking mechanism between phenylboronic acid groups and hydroxylated carbon nanotubes (OHCNT) and positive electrode active particles, as well as the self-cross-linking between phenylboronic acid to form a cycloborane structure, forming a special three-dimensional conductive network structure, thereby improving the mechanical strength, conductivity, cycle performance and stability of the binder; from the battery performance test results of Examples 1-5 and Examples 6-7, it can be seen that when phenylboronic acid When the mass ratio of the polyacrylic acid compound to the phenylboronic acid compound is in the range of 0.19-1.33, the peeling force, interfacial peeling strength, viscosity (Pa·s), conductivity of the binder and the cycle stability of the battery are better; from the battery performance test results of Example 1, Examples 8-10 and Examples 11-12, it can be seen that when the mass of the polyacrylic acid compound modified by the phenylboronic acid compound and the hydroxylated carbon nanotubes is in the range of 1.0-6.0, the peeling force, interfacial peeling strength, viscosity (Pa·s), conductivity of the binder and the cycle stability of the battery are better; from the battery performance test results of Example 1, Examples 13-15 and Examples 16-17, it can be seen that when the mass ratio of the activator and the polyacrylic acid compound is in the range of 0.53-1.60, the peeling force, interfacial peeling strength, viscosity (Pa·s), conductivity of the binder and the cycle stability of the battery are better.
[0063] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.
Claims
1. A positive electrode sheet for a battery, characterized in that: The invention comprises a positive electrode active material and a binder. The binder is a product obtained by cross-linking a polyacrylic acid compound modified by a phenylboronic acid compound and a hydroxylated carbon nanotube.
2. A battery positive electrode sheet according to claim 1, characterized in that: The mass ratio of the phenylboric acid compound to the polyacrylic acid compound is 0.19-1.
33.
3. A battery positive electrode sheet according to claim 1, characterized in that: The mass ratio of the phenylboronic acid compound modified polyacrylic acid compound to the hydroxylated carbon nanotube is 1.0-6.
0.
4. A battery positive electrode sheet according to claim 1, characterized in that: The raw materials of the binder also include an activator, and the mass ratio of the activator to the polyacrylic acid compound is 0.53-1.
60.
5. A battery positive electrode sheet according to claim 4, characterized in that: The activator is at least one of 1-ethyl-(3-dimethylaminopropyl)carbodiimide, dicyclohexylcarbodiimide, and N,N'-diisopropylcarbodiimide.
6. A battery positive electrode sheet according to claim 1, characterized in that: The phenylboronic acid compound is at least one of 3-aminophenylboronic acid, 2-aminophenylboronic acid, 4-aminophenylboronic acid, [3-(2-aminoethyl)phenyl]boric acid and 3-aminomethylphenylboronic acid.
7. A battery positive electrode sheet according to claim 1, characterized in that: The polyacrylic acid compound includes at least one of polyacrylic acid, polymethacrylic acid, sodium polyacrylate, lithium polyacrylate, sodium polymethacrylate, and lithium polymethacrylate.
8. A battery positive electrode sheet according to any one of claims 1 to 7, characterized in that: The polyacrylic acid compound is modified by phenylboronic acid compound and cross-linked with hydroxylated carbon nanotubes, including: S1. Dissolve a polyacrylic acid compound and a base in water, add an aqueous solution of a phenylboric acid compound to obtain a mixed solution, cool the mixed solution to 2°C-7°C, add an activator, and react for 10-14 hours to obtain a polyacrylic acid compound modified with a phenylboric acid compound; S2: adding hydroxylated carbon nanotubes and dispersant into water and ultrasonicating for 1-3 hours to obtain a dispersion, and mixing the dispersion with the polyacrylic acid compound modified with the phenylboronic acid compound.
9. A battery positive electrode sheet according to claim 1, characterized in that: The positive electrode active material includes at least one of lithium iron phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide.
10. A battery, characterized in that: A battery positive electrode sheet comprising any one of claims 1 to 9, wherein the battery is a lithium ion battery, a semi-solid battery or a solid-state battery.
Citation Information
Patent Citations
Phenylboronic acid-functionalized multi-walled carbon nanotube magnetic nanocomposite material as well as preparation method and application thereof
CN112574431A
Polymer binder, physical-chemical double-crosslinking conductive polymerization network, and preparation method and application of polymer binder and physical-chemical double-crosslinking conductive polymerization network
CN116445104A
Flame resistant quasi-solid and solid electrolyte for lithium ion and lithium metal batteries and method of production
CN116964808A
Polymer binder, self-healing conductive cross-linked polymerization network and preparation method and application of self-healing conductive cross-linked polymerization network
CN118562439A
Negative plate and battery
CN118867134A
Cited By
Negative electrode coating material production method, negative electrode coating material and lithium ion battery
CN121394371A
Production method of negative electrode coating material, negative electrode coating material and lithium ion battery
CN121394371B